Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10534-012-9547-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and electrochemical characterization of gold(I) and gold(III) complexes with glyoxaldehyde bis(thiosemicarbazones): cytotoxicity against human tumor cell lines and inhibition of thioredoxin reductase activity

Abstract: Complexes [Au(2)(H(2)Gy3DH)(2)]Cl(2) (1), [Au(H(2)Gy3Me)]Cl(3) (2) and [Au(H(2)Gy3Et)]Cl(3) (3) were obtained with glyoxaldehyde bis(thiosemicarbazone) (H(2)Gy3DH) and its N(3)-methyl (H(2)Gy3Me) and N(3)-ethyl (H(2)Gy3Et) derivatives. The bis(thiosemicarbazones) and their gold(I) and gold(III) complexes exhibited anti-proliferative activity against HL-60, Jurkat (leukemia) and MCF-7 (breast cancer) cells at 10 μmol L(-1). Complex (2) was able to in vitro inhibit thioredoxin reductase (TrxR) activity, which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…The following trend of stable adduct formation with Sec was proposed: 122 > 124 > 123 > 125 = 126 . Beraldo and co‐workers reported that gold (III) complex ( 127 , Figure C) is able to inhibit the rat liver TrxR activity with an IC 50 value of 2.90 μM, and potently inhibits the growth of HL‐60, Jurkat, HCT‐116, and MCF‐7 cells . In addition, the gold (III) complex [Au(H py 2Ac4mT)Cl 2 ]ClH 2 O also inhibits 75% of rat liver TrxR activity .…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 94%
“…The following trend of stable adduct formation with Sec was proposed: 122 > 124 > 123 > 125 = 126 . Beraldo and co‐workers reported that gold (III) complex ( 127 , Figure C) is able to inhibit the rat liver TrxR activity with an IC 50 value of 2.90 μM, and potently inhibits the growth of HL‐60, Jurkat, HCT‐116, and MCF‐7 cells . In addition, the gold (III) complex [Au(H py 2Ac4mT)Cl 2 ]ClH 2 O also inhibits 75% of rat liver TrxR activity .…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 94%
“…Gold(III) compounds have also attracted much attention for their outstanding cytotoxic activity, structural and electronic similarity (square planar, d 8 ) to platinum(II) complexes, (Gabbiani et al 2007;Lessa et al 2012;Maiore et al 2012). One of the main obstacles for their use in medicine is their low stability in physiological conditions which can be increased by coordination of multidentate ligands.…”
mentioning
confidence: 99%
“…Furthermore, the ESI + MS spectrum shows an exclusive [M] + complex ion peak with no evidence for the formation of gold(I) compounds, a common finding for gold(III) thiosemicarbazone derivatives. 14,28,29 Concerning 4-Cl stability, through observation of UV−vis-NIR absorption spectra (Supplementary Figure 1), it was possible to verify that incubation in DMSO and RPMI (10% of SBF) during 72 h could not significantly change the complex structure. Although stable in the aforementioned media, in PBS, a great decrease in the 416 nm band could lead one to erroneously believe there was the complex consumption during the stability experiment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%